A Novel T55A Variant of Gsα Associated with Impaired cAMP Production, Bone Fragility, and Osteolysis. (7th August 2016) - Wentworth, Kelly; Hsing, Alyssa; Urrutia, Ashley; Zhu, Yan; Horvai, Andrew E.; Bastepe, Murat; Hsiao, Edward C.
Abstract : G-protein coupled receptors (GPCRs) mediate a wide spectrum of biological activities. The GNAS complex locus encodes the stimulatory alpha subunit of the guanine nucleotide binding protein (G s α ) and regulates production of the second messenger cyclic AMP (cAMP). Loss-of-function GNAS mutations classically lead to Albright's Hereditary Osteodystrophy (AHO) and pseudohypoparathyroidism, often with significant effects on bone formation and mineral metabolism. We present the case of a child who exhibits clinical features of osteolysis, multiple childhood fractures, and neonatal SIADH. Exome sequencing revealed a novel de novo heterozygous missense mutation of GNAS (c.163A<G, p.T55A) affecting the p-loop of the catalytic G s α GTPase domain. In order to further assess whether this unique mutation resulted in a gain or loss of function of G s α, we introduced the mutation into a rat GNAS plasmid and performed functional studies to assess the level of cAMP activity associated with this mutation. We identified a 64% decrease in isoproterenol-induced cAMP production in vitro, compared to wild type, consistent with loss of G s α activity. Despite a significant decrease in isoproterenol-induced cAMP production in vitro, this mutation did not produce a classical AHO phenotype in our patient; however, it may account for her presentation with childhood fractures and osteolysis.